Colonic Aging and Colorectal Cancer: An Unignorable Interplay and Its Translational Implications - Qiyan Yin; Fen Qin; Fangliu Gan; Guangxi Zhao; Ronghua Chen; Yue Wen; Xueyang Hua; Fugui Zeng; Yuezheng Zhang; Yuliang Xiao; Wenbing Xie; Yong Tao (Biology)
Colorectal cancer (CRC) incidence increases markedly with age, yet chronological age is an inadequate proxy for the complex biological processes involved. Colon aging, the intrinsic biological aging of the colonic tissue, is emerging as a crucial, active driver of CRC development. This review comprehensively analyzes the interplay between colon aging and CRC pathogenesis by examining fundamental hallmarks of aging—such as altered tissue homeostasis, epigenetic dysregulation, and microenvironmental shifts including chronic inflammation (inflammaging), gut microbiome dysbiosis, and extracellular matrix remodeling—manifest specifically within the aging colon to synergistically foster a pro-tumorigenic environment. Key findings synthesized from the literature highlight the critical roles of impaired colonic stem cell function, epithelial barrier disruption (“leaky gut”), persistent low-grade inflammation, and altered microbial communities and their metabolites in promoting CRC initiation and progression. Translating this mechanistic understanding holds significant promise: insights from colon aging research can inform novel biomarkers for improved early detection and risk stratification, guide the development of personalized preventative strategies and therapeutic interventions targeting aging pathways, and underpin public health initiatives focused on healthy colon aging. Ultimately, recognizing colon aging as a modifiable contributor to CRC offers a powerful avenue to potentially reduce CRC incidence and enhance patient outcomes, particularly in the vulnerable aging population.